THE MYTH OF PURSUING HAPPINESS IN THE PURSUIT OF HAPPYNESS - Muludi, Riza Rahayu; Adi, Ida Rochani (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
This research aims to examine how to pursue happiness constructs Americans in the film The Pursuit of Happyness (2006). Pursuing happiness is included in one of the American Dreams which means that everyone in America deserves their happiness. To investigate the analyses, this study uses Roland Barthes' semiotic analysis to find out the happiness in Americans. The results show that pursuing happiness is categorized as one of the American myths and the American characteristics. The characteristics of freedom, happiness, and success describe the American character in pursuing happiness as the myth. In addition, pursuing happiness illustrates the similarity of the narrative when compared to the myth. It analyses in social and cultural of Americans' lives.